Penegakan Hukum Terhadap Tindak Pidana Yang Berkaitan Dengan Kerusuhan Suporter Sepak Bola Di Surakarta (Studi Kasus di Polresta Surakarta) - Aryawan, Tiar; , Kuswardani, S.H., M.Hum; , Bambang Sukoco S.H.,M.H (2016)
The purpose of this study to determine criminal offenses arising in rioting fans, to see the passage of the law enforcement for alleged criminal offenses arising in the riots, and know the obstacles that arise in law enforcement for alleged criminal offenses relating to the riots football supporters in Surakarta, The research method uses normative-empirical approach or juridical-empirical. The data source consists of primary data that interview, while the secondary data source of primary law, secondary and tertiary. Data were collected by literature study and field studies and interviews. Data analysis used descriptive analysis-critical. The results showed a criminal offense that arises is mostly beatings and ill-treatment, in which the handling of the offense is not running optimally due to lack of witness testimony and the absence of sufficient evidence. Constraints in law enforcement against alleged criminal offenses relating to the riots of supporters influenced by several factors: weak law enforcement, lack of community participation in providing testimony and the lack of facilities and support facilities in facilitating the process of evidence.